Revision of the Australian species of the ant genus Anochetus (Hymenoptera: Formicidae) - Shattuck, Steven O.; Slipinska, Ewa (Zootaxa, 2012)
The Australian species of the ponerine ant genus Anochetus are revised. Fourteen species are known from Australia with eight described here for the first time (alae n. sp, armstrongi McAreavey, avius n. sp., graeffei Mayr, isolatus Mann, paripungens Brown, rectangularis Mayr, renatae n. sp., rufolatus n. sp., rufostenus n. sp., turneri Forel, veronicae n. sp., victoriae n. sp., wiesiae n. sp.). Twelve are endemic to Australia while two are shared with Australia’s northern neighbours. Most species are restricted to tropical regions with only two known from southern Australia. While the majority of species are found in forested habitats, ranging from rainforest to dry sclerophyll woodlands, in southern regions they extend into drier shrub and bush dominated sites.